2019
DOI: 10.7567/1882-0786/ab42c2
|View full text |Cite
|
Sign up to set email alerts
|

Preventing trench defect formation in InGaN epilayers using Ga-migration-enhanced epitaxy

Abstract: The growth of InGaN by Ga-migration-enhanced epitaxy using metalorganic chemical vapor deposition is reported. Trench defects, which are usually associated with the generation of basal-plane stacking faults (BSFs), can be significantly diminished by this method. The surface morphology and luminescence characteristics of the deposited InGaN are consequently improved. It is demonstrated that the Ga-migration-enhanced epitaxy can inhibit the generation of BSFs and thus prevent the formation of trench defects in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…29,30 Besides, previous research studies have suggested that more BSFs are formed in the case of low atomic mobility. 8,31,32 The BSFs may induce stacking mismatch boundaries and then trigger the formation of V-pits, resulting in the clustered V-pits in trench defects. 33,34 3.2.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…29,30 Besides, previous research studies have suggested that more BSFs are formed in the case of low atomic mobility. 8,31,32 The BSFs may induce stacking mismatch boundaries and then trigger the formation of V-pits, resulting in the clustered V-pits in trench defects. 33,34 3.2.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the In adatoms act as surfactants in the epitaxy process of InGaN, and That is, the quantity of metal adatoms is probably less than 1 ML, resulting in lowered surface of Ga adatoms and the subsequent formation of BSFs and related trench defects. 8 Moreover, PL characteristics were also measured using a Horiba JYHR800 spectrometer with a 325 nm excitation laser beam, as shown in Figure 5b. In the measurements, the diameter of a laser beam spot is ∼30 μm, and the incident power is ∼0.31 mW.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations